Turning policy implications into policy impact: Lessons from behavioral science in financial markets - Alycia Chin; Katherine G. Carman; Adam W. Craig; Jonathan A. Cook; David B. Zimmerman (Proceedings of the National Academy of Sciences, 2026)
We describe how research can inform policymaking. We begin by summarizing the policy formation process, offering a framework illustrating how interactions between scientists and policymakers can provide mutual benefits. We then describe four research initiatives from the Securities and Exchange Commission’s Office of Investor Research (OIR) as examples of how behavioral sciences can help inform policymakers. The first initiative established a probability-based nationally representative survey panel focused on US investor behavior. The remaining three examined investor communications for mutual fund benchmarks, emerging annuities (known as registered index-linked annuities), and mutual fund fee visuals. We conclude by synthesizing our work and describing practices that can help scientists have policy impact, not just policy implications.